THE IMPACT OF THE SOUTH CHINA SEA GEOPOLITICAL CONFLICT ON INDONESIA'S INTERNATIONAL TRADE: THE MEDIATING ROLE OF RISK PERCEPTION AND LOGISTICS EFFICIENCY - Riza Aini; Leni Hartati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Geopolitical tensions in the South China Sea (SCS) represent a significant external factor that may affect Indonesia’s international trade. As one of the world’s major maritime trade routes, escalating conflicts in the SCS can increase economic uncertainty and weaken national logistics performance. This study aims to analyze the impact of South China Sea geopolitical conflict on Indonesia’s international trade by examining the mediating roles of risk perception and logistics efficiency. The study employs a quantitative causal explanatory approach using quarterly time series data from 2020Q1 to 2024Q4 (n = 20). Geopolitical conflict is proxied by the Geopolitical Risk Index (GPR), risk perception is measured by Indonesia’s World Uncertainty Index (WUI), logistics efficiency is represented by the Logistics Performance Index (LPI), and international trade is measured by total export and import values. Data analysis methods include descriptive statistics, Pearson correlation, linear regression, and mediation tests using the Baron and Kenny approach and the Sobel test. The results show that geopolitical conflict has a significant positive effect on risk perception and a significant negative effect on logistics efficiency. Geopolitical conflict also has a significant negative effect on international trade in the direct model. However, after incorporating the mediating variables, the direct effect becomes insignificant. Risk perception and logistics efficiency are found to fully mediate the relationship between geopolitical conflict and Indonesia’s international trade.